The Factors Affecting the Quality of Sleep in Shift-Working Nurses - Kim, Tae-Kyung; Kang, Hwa-Jung (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: This is descriptive research aimed at identifying the factors affecting the quality of sleep in nurses working on shifts at a general hospital. Methods/Statistical analysis: Research was conducted in 141 nurses with at least 3 years of career in work on shifts at a local general hospital by using a self-administered, structured questionnaire concerning the quality of sleep, job satisfaction, and organizational commitment. Data analysis was performed through t-test, one-way ANOVA, Pearson correlation coefficient, and step wise multiple regression by using SPSS/WIN 23.0. Findings: They scored 3.55+.54 out of 5 for job satisfaction, 3.28+.56 for organizational commitment, and 1.26+.87 out of 4 for the quality of sleep; the lower score, the higher quality of sleep. Job satisfaction was positively correlated with organizational commitment and was negatively correlated with the quality of sleep. Controlling the general characteristics, job satisfaction and organizational commitment significantly affected the lower quality of sleep (Odds Ratio [OR]=4.56, 95% Confidence interval [CI]=1.02-20.49; OR=0.97, 95% CI=0.94-0.99, respectively). This model accounted for 19.5% of the quality of sleep. Improvements/Applications: It is necessary to develop a nursing intervention strategy for improving the quality of sleep and, consequently, job satisfaction and organizational commitment, and to develop, apply, and evaluate the effectiveness of a psychological intervention training reinforcement program that can contribute to the improvement in the quality of sleep for shift-working nurses.